2019
DOI: 10.1111/jace.16602
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced insulating and piezoelectric properties of BiFeO3‐BaTiO3‐Bi0.5Na0.5TiO3 ceramics with high Curie temperature

Abstract: BiFeO3‐BaTiO3 ceramics are promising lead‐free piezoelectric ceramics due to their high piezoelectric properties and high Curie temperature, but their high leakage current density makes the poling difficult. In this study, a decreased leakage current density by three orders of magnitude was obtained in Bi0.5Na0.5TiO3 (BNT) added 0.67BiFeO3‐0.33BaTiO3 (BF‐BT) ceramics. It was found that the largely improved insulating properties benefit from the reduced oxygen vacancies and weak reduction of Fe3+ to Fe2+ as con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 61 publications
(129 reference statements)
1
19
0
Order By: Relevance
“…3(c) and S1. † [20][21][22][23][24][25][26][27][28][29][30][31][32][33] Only a slight increase of the 3 r value from ∼800 at x = 0 to ∼880 at x = 0.003 (increase by ∼10%) can be observed even though the d 33 value exhibits an obvious increase from ∼180 to ∼240 pC N −1 (increase by ∼35%) in the BF(MN) x -BT-BNT ceramics. By comparison, a good balance between T c and d 33 values has been realized in the x = 0.003 composition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3(c) and S1. † [20][21][22][23][24][25][26][27][28][29][30][31][32][33] Only a slight increase of the 3 r value from ∼800 at x = 0 to ∼880 at x = 0.003 (increase by ∼10%) can be observed even though the d 33 value exhibits an obvious increase from ∼180 to ∼240 pC N −1 (increase by ∼35%) in the BF(MN) x -BT-BNT ceramics. By comparison, a good balance between T c and d 33 values has been realized in the x = 0.003 composition.…”
Section: Resultsmentioning
confidence: 99%
“…Instead, it is suggested that the addition of (Mg 2/3 Nb 1/3 ) 3+ would induce the short-range chemical order between the large Mg 2+ ion center and the average distribution of the relatively small Fe 3+ /Fe 2+ and Nb 5+ ions on the adjacent octahedral site to minimize strain energy (CN = 6, R Mg 2+ = 0.72 Å, R Fe 3+ = 0.55 Å, R Fe 2+ = 0.62 Å, and R Nb 5+ = 0.64 Å). 26,54 As a result, the negatively charged AMgO 3 (A = Bi, Ba, Na) subcell would restrain the reduction of the valence of Fe ions on the adjacent octahedral site due to the electrostatic driving force between Mg 2+ and Fe 3+ /Fe 2+ ions. The increase in the amount of Fe 3+ ions would be benecial for the increase of the lattice distortion of the R phase as conrmed by the XRD data shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…All ceramics possess perovskite structures with a small number of impure phases Bi 25 FeO 40 (ICSD#62719) due to 5% Bi 2 O 3 excess, indicating that NaTaO 3 enter the solid solution formed by the BiFeO 3 –BaTiO 3 well. 21,33 Furthermore, the coexistence and variations of the phase content are determined by enlarging the diffraction peaks at (110) pc , (111) pc , and (200) pc in the BF–BT ceramics [see Fig. 2(a 2 )].…”
Section: Resultsmentioning
confidence: 99%
“…All ceramics possess perovskite structures with a small number of impure phases Bi 25 FeO 40 (ICSD#62719) due to 5% Bi 2 O 3 excess, indicating that NaTaO 3 enter the solid solution formed by the BiFeO 3 -BaTiO 3 well. 21,33 Furthermore, the coexistence and variations of the phase content are determined by enlarging the diffraction peaks at (110) pc , (111) pc , and (200) pc in the BF-BT ceramics [see Since Ta 5+ has a greater electronegativity than Fe 3+ , it is more attractive and strongly attached to O 2+ , resulting in an increase in the degree of distortion of the oxygen octahedron as more Ta 5+ enters the lattice; 35,36 the second is the effect of orbital hybridization, where the 5d state of Ta 5+ will substantially overlap with the 2p state of O 2+ , establishing a more stable covalent bond than Fe-O. 37,38 Combining SEM and XPS analyses, it can be known that vacancies created by heterovalent elements promote ion transport, resulting in the average grain size and density reaching the maximum at x ¼ 0.008 (see Fig.…”
Section: Phase Structurementioning
confidence: 99%
“…Figure e displays the fluorescence spectra of the Er‐KNLN ceramics under 380 nm excitation, and a conspicuous peak of oxygen vacancy defects at ≈800 nm can be seen. [ 44,45 ] Furthermore, the content of VnormalO was checked by the XPS O 1s results in Figure 8a–c. The broad peak of O 1s usually can be decomposed into three peaks, 533 eV (O3), 531 eV (O2), and 529 eV (O1) corresponding to weakly surface‐adsorbed oxygen or hydroxyl groups, oxygen vacancies, and lattice oxygen, respectively.…”
Section: Resultsmentioning
confidence: 99%